Biofortification of fruits for improved nutritional and postharvest quality - Mir, Hidayatullah; Singh, Preeti; Homa, Fozia (Journal of Postharvest Technology, 2015)
Deficiency of micronutrients and vitamins in human body can lead to diseases, disabilities, stunted physical and mental growth. Biofortification of food crops can be a solution for overcoming problems of malnutrition and hidden hunger. Biofortification is the process of increasing deficient micronutrients in the desirable plant parts through fertilization, breeding and transgenic approach. It is a cost-effective and sustainable approach to provide nutrition to the under-privileged population. Other than biofortification of staple food crops, fruit crops can also be targeted. Fruits are already rich in health promoting substances like vitamins, minerals and antioxidants which are required for proper functioning of human body. Fruits like banana, strawberry, apple, mango, etc. have been biofortified adopting various techniques. The two challenges that are faced in the process of biofortification of fruits are the development of nutrient rich variety and adoption of improved variety by the farmers.